1995
DOI: 10.1016/0029-7844(94)00376-o
|View full text |Cite
|
Sign up to set email alerts
|

Puerperal seizures after postdural puncture headache

Abstract: We propose that cerebral vasoconstriction is the mechanism for post-dural puncture headaches and seizures. Anatomic brain displacement may incite this vasospasm. This mechanism could also be the cause of cranial nerve palsies that have been described after dural puncture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 10 publications
0
23
0
1
Order By: Relevance
“…Previous studies have demonstrated that vasospasm can occur during the acute phase of PRES (16 -18). An earlier report described eight postpartum women with postdural puncture headache who developed cortical blindness and seizure (19); angiography and xenon flow studies performed in three of them showed diffuse cerebral artery vasospasm (19). In the current patient, diffuse cerebral artery vasospasm, possibly due to the traction of this vessel by anatomic brain displacement, could provide an explanation for the development of PRES after spinal anesthesia.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies have demonstrated that vasospasm can occur during the acute phase of PRES (16 -18). An earlier report described eight postpartum women with postdural puncture headache who developed cortical blindness and seizure (19); angiography and xenon flow studies performed in three of them showed diffuse cerebral artery vasospasm (19). In the current patient, diffuse cerebral artery vasospasm, possibly due to the traction of this vessel by anatomic brain displacement, could provide an explanation for the development of PRES after spinal anesthesia.…”
Section: Discussionmentioning
confidence: 81%
“…Clinical and radiological features of PRES include headache, encephalopathy, seizures, cortical visual changes, and parieto-occipital white matter edema visualized on neuroimaging modalities 12 . In this case, headache and convulsion in early post partum period without proteinuria might be due to cerebral venous sinus thrombosis, subarachnoid hemorrhage and postdural punctures seizures in the postpartum period 13 . The diagnosis of PRES was made following the typical radiological findings of bilateral, symmetrical cortical and subcortical vasogenic edema in combination with the characteristic presenting features.…”
Section: Discussionmentioning
confidence: 75%
“…[8][9][10][11] With this case report, we suggest adding multiple sclerosis and PDPH to the list of possible predisposing factors and IV caffeine to the list of trigger factors for PRES. …”
Section: Discussionmentioning
confidence: 99%